Methodology of physical exercise: A proposal and reliability of a questionnaire for fitness professionals - Francys Paula Cantieri; Antonio Carlos Gomes; Gustavo Aires de Arruda; Diogo Henrique Constantino Coledam; Edineia Aparecida Gomes Ribeiro; Mauro Virgilio Gomes de Barros; Ágata Cristina Marques Aranha (Baltic Journal of Health and Physical Activity, 2021)
Background: Several benefits of physical exercise for health are described in the literature and knowing the methodology adopted by professionals is relevant. Objective: Proposal and analysis of the psychometric properties of a questionnaire on the methodological practice of professionals working in the fitness area. Material and methods: Design: Reproducibility study. Method: The questionnaire was prepared following the steps: search for existing instruments, elaboration of the questions, pretesting (n = 30), face/content validity (n = 5), and reliability (n = 333). The internal consistency (Cronbach's Alpha), magnitude of the association between nominal questions (Cramer's V or Phi) and test-retest reliability (Kappa coefficient) were analyzed. Results: The Cronbach's Alpha value was 0.78 (95%CI: 0.70–0.83). The mean value of Cramer's V was 0.16 (±0.06). Test-retest reliability values ranged from fair to good, with percentage agreement ranging from 48.8% (95%CI: 37.8–59.8) to 90.3% (95%CI: 81.3–95.4). Conclusions: The questionnaire serves the purpose for which it was created and can be applied to identify how professionals structure their practices.